Memorandum of understanding between Universiti Teknologi MARA and University of Perpetual Help System Dalta (UPHSD), Las Pinas Campus, Philippines / Fakulti Kejuruteraan Elektrik - Universiti Teknologi MARA, Fakulti Kejuruteraan Elektrik (Universiti Teknologi MARA (UiTM), 2019)
UiTM and UPHSD, recognizing their strengths and the benefits to their respective universities from the establishment of international links to foster academic cooperation and research.